A PP composite material and its preparation method and application

By combining PP grafts, PE resins and tackifying resins in PP resin, the problems of low peel strength and poor moldability during the bonding process between metal and plastic are solved, and high peel strength and PP composite material with excellent moldability.

CN117511060BActive Publication Date: 2025-02-21CHENGDU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311556565.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2025-02-21
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

The existing PP adhesives have problems of low peel strength and poor moldability during the bonding process between metal and plastic, which affects their effectiveness in corrosion protection and weight reduction applications.

Method used

By combining PP grafts, PE resin and tackifying resin on the basis of PP resin, the melt flow rate and graft rate are adjusted to improve adhesive performance and moldability.

Benefits of technology

The high peel strength and excellent moldability of PP composite materials are achieved. The peel strength of the product is above 135N/m and the melt strength is above 20NM, which meets the needs of extrusion molding and blown film forming.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004561232470000061
    Figure BDA0004561232470000061
  • Figure BDA0004561232470000071
    Figure BDA0004561232470000071
  • Figure BDA0004561232470000072
    Figure BDA0004561232470000072
Patent Text Reader

Abstract

The invention discloses a PP composite material and a preparation method and application thereof, belonging to the technical field of polymer engineering plastics; the PP composite material provided by the invention comprises the following components by weight: 40-70 parts of PP resin, 20-40 parts of PP grafts, 8-20 parts of tackifying resin, and 5-15 parts of PE resin. The PP composite material provided by the invention uses a PP resin within a specific intrinsic viscosity range as a matrix, and simultaneously compounding a PP graft, a PE resin, and a tackifying resin, thereby being able to achieve excellent bonding performance and formability of the PP composite material, and the obtained product has high peeling strength and good formability; and the preparation method of the composite material provided by the invention is simple, which is conducive to actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer engineering plastics, and in particular relates to a PP composite material and a preparation method and application thereof. Background Art

[0002] Lightweight, environmental protection, energy and energy saving have been hot topics in recent years, among which replacing steel with plastic is a good solution. Polymer materials have good toughness, acid and alkali resistance, hydrolysis resistance and other properties, so they are widely used. However, polymer materials also have many problems, such as: rigidity is much worse than metal, and anti-collision and explosion-proof performance are also much worse. In some cases where performance is excessive, or some metal parts are underground or soaked in water for a long time, or outdoors, a layer of polymer resin can be coated or coated on the metal to play a role in corrosion prevention and weight reduction. As we all know, metals are incompatible with polymer materials and difficult to bond, and adhesives are usually used as bonding layers.

[0003] PP has the advantages of low density, corrosion resistance, and low cost, and is widely used in the automotive, home appliance, packaging and other industries. In the anti-corrosion 3PP pipes, PP metal pipes, metal composite PP fiber sheets, etc., PP adhesives are often used as bonding layers as a bridge for bonding metals and plastics. PP adhesive modification technology improves the polarity and activity of materials by adding PP grafted maleic anhydride, tackifying resin, etc., so that the two can be bonded. PP grafted maleic anhydride, because its main monomer is propylene, the side methyl group is more active, and after adding initiators, it will cause molecular chain scission, greatly improve the melt index (melt index compared to the initial value by tens or hundreds of times), and other properties will also decrease. At the same time, due to the large steric hindrance of the side methyl group, the grafting rate of PP grafted maleic anhydride is relatively low. High melt index and low viscosity will affect the later molding, such as low viscosity is not conducive to extrusion and blown film molding. In addition, the grafting rate is the key to bonding. The above shortcomings limit its use to a certain extent. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a PP composite material with high peel strength and excellent formability, and a preparation method and application thereof.

[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a PP composite material, the PP composite material comprising the following components in parts by weight: 40-70 parts of PP resin, 20-40 parts of PP graft, 8-20 parts of tackifying resin, and 5-15 parts of PE resin;

[0006] The melt flow rate of the PP resin is ≤15g / 10min;

[0007] The PP graft is a maleic anhydride grafted PP matrix resin, and the melt flow rate of the PP graft is less than 100g / 10min; the PP graft can be a commercial product or homemade;

[0008] The melt flow rate of the PE resin is 0.1-10 g / 10 min, and the melt strength is greater than 30 NM.

[0009] The PP composite material provided by the present invention uses a PP resin within a specific characteristic viscosity range as a matrix, and is compounded with a PP graft, a PE resin, and a tackifying resin, so that the PP composite material can achieve excellent bonding performance and formability, and the obtained product has high peeling strength and good formability. Specifically, the PP graft added in the present invention is a homemade product, and the melt flow rate of the prepared PP graft is less than 100g / 10min, and a PP graft with a lower melt index and a high grafting rate can be obtained; further selecting a PE resin in a suitable melt flow rate range and melt strength range can reinforce the low viscosity performance of the PP resin and the PP graft, and compounding a tackifying resin at the same time can achieve that the PP composite material has excellent bonding performance and high melt strength, thereby meeting the requirements of extrusion molding and blown film molding, and expanding the scope of use.

[0010] The melt flow rate of PP resin is measured with reference to ISO 1133-1-2011, and the test conditions are 230°C / 2.16kg.

[0011] The melt flow rate of the PP graft is measured with reference to ISO 1133-1-2011, and the test conditions are 230°C / 0.325kg.

[0012] The mass percentage of ethylene in the PP matrix resin is determined by referring to the method in the document "Determination of ethylene content in random copolymer polypropylene by Fourier transform infrared spectroscopy".

[0013] The melt flow rate of PE resin is determined with reference to ISO 1133-1-2011, and the test conditions are 190°C / 2.16kg; the melt strength is measured by a melt strength tester, and the force at break is recorded at 190°C. The force at which the melt bundle breaks is defined as the "melt strength".

[0014] The PP resin described in the present invention may be homopolymer, copolymer or random copolymer polypropylene; the PE resin described in the present invention may be at least one of low-density polyethylene, linear low-density polyethylene and high-density polyethylene.

[0015] As a preferred embodiment of the PP composite material of the present invention, the PP composite material comprises the following components in parts by weight: 45-65 parts of PP resin, 25-35 parts of PP grafts, 10-15 parts of tackifying resin, and 8-12 parts of PE resin.

[0016] The inventors have found that when the mass fraction of the further component is within the above range, the comprehensive performance of the obtained product is better.

[0017] As a preferred embodiment of the PP composite material of the present invention, at least one of the following (a)-(c) is included:

[0018] (a) the melt flow rate of the PP resin is 0.3-12 g / 10 min;

[0019] (b) the melt flow rate of the PP graft is 15-95 g / 10 min, the PP matrix resin is a copolymer of propylene and ethylene, and the mass percentage of ethylene is 3-25%;

[0020] (c) The melt flow rate of the PE resin is 0.10-8.5 g / 10 min.

[0021] For example, the melt flow rate of the PP resin can be any point value between 0.3-12 g / 10 min or a range value consisting of any two points, such as 0.4-9 g / 10 min, 0.4-6 g / 10 min, 6-9 g / 10 min, etc., or 0.3 g / 10 min, 0.4 g / 10 min, 1 g / 10 min, 1.5 g / 10 min, 2 g / 10 min, 2.5 g / 10 min, 3 g / 10 min, 3.5 g / 10 min, 4 g / 10 min, etc. The point values ​​of 0.3-12g / 10min can be used as follows: min, 4.5g / 10min, 5g / 10min, 5.5g / 10min, 6g / 10min, 6.5g / 10min, 7g / 10min, 7.5g / 10min, 8g / 10min, 8.5g / 10min, 9g / 10min, 9.5g / 10min, 10g / 10min, 12g / 10min, etc. are not listed here one by one due to space limitations. Within the range of 0.3-12g / 10min given in the present invention, the effects of the present invention can be achieved.

[0022] Preferably, the melt flow rate of the PP resin is 6-9 g / 10 min. Within the range of 6-9 g / 10 min, the comprehensive effect of the obtained product is more excellent.

[0023] For example, the melt flow rate of the PP graft can be any point value between 15-95 g / 10min or a range value consisting of any two points, such as 20-40 g / 10min, 20-60 g / 10min, 40-60 g / 10min, etc., or 15 g / 10min, 20 g / 10min, 25 g / 10min, 30 g / 10min, 35 g / 10min, 40 g / 10min. , 45g / 10min, 50g / 10min, 55g / 10min, 60g / 10min, 65g / 10min, 70g / 10min, 75g / 10min, 80g / 10min, 85g / 10min, 90g / 10min, 95g / 10min and other point values ​​are not listed here one by one due to space limitations. Within the range of 15-95g / 10min given in the present invention, the effect of the present invention can be achieved. In the PP matrix resin, the mass percentage of ethylene can be any point value between 3-25% or a range value consisting of any two points, such as 5-20%, 2-15%, 10-15%, etc., or 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, etc. Due to space limitations, they are not listed here one by one. Within the range of 3-25% given in the present invention, the effect of the present invention can be achieved.

[0024] Preferably, the melt flow rate of the PP graft is 40-60g / 10min, and the mass percentage of ethylene in the PP matrix resin is 10-15%; when the melt flow rate of the PP graft is 40-60g / 10min and the mass percentage of ethylene in the PP matrix resin is 10-15%, the comprehensive effect of the obtained product is more excellent.

[0025] For example, the melt flow rate of the PE resin can be any point value between 0.10-8.5 g / 10 min or a range value consisting of any two points, such as 0.11-3.5 g / 10 min, 0.11-2 g / 10 min, 2-3.5 g / 10 min, etc., or 0.11 g / 10 min, 0.15 g / 10 min, 0.2 g / 10 min, 0.5 g / 10 min, 0.8 g / 10 min, 1 g / 10 min, 1.5 g / 10 min, 2 g / 1 The point values ​​of 0.10g / 10min, 2.5g / 10min, 3g / 10min, 3.5g / 10min, 4g / 10min, 4.5g / 10min, 5g / 10min, 5.5g / 10min, 6g / 10min, 6.5g / 10min, 7g / 10min, 7.5g / 10min, 8g / 10min, 8.5g / 10min, etc. are not listed here one by one due to space limitations. The effects of the present invention can be achieved within the range of 0.10-8.5g / 10min given in the present invention.

[0026] Preferably, the melt flow rate of the PE resin may be 2-3.5 g / 10 min. When the melt flow rate of the PE resin is further preferably 2-3.5 g / 10 min, the obtained product has a higher melt strength and better bonding performance.

[0027] As a preferred embodiment of the PP composite material of the present invention, the tackifying resin is at least one of rosin resin, petroleum resin, EVA, EMA, and EEA.

[0028] Preferably, the tackifying resin is petroleum resin.

[0029] The inventors have found that when the tackifying resin is further selected as petroleum resin, the comprehensive performance of the obtained product is better.

[0030] As a preferred embodiment of the PP composite material of the present invention, the preparation method of the PP graft is: PP matrix resin, initiator and maleic anhydride are mixed, melt-extruded, drawn into strips and pelletized to obtain the PP graft.

[0031] Preferably, in the method for preparing the PP graft, the temperature of melt extrusion is 170-210°C.

[0032] Preferably, based on the PP matrix resin, the added amount of the initiator is 0.05-0.15%, and the added amount of the maleic anhydride is 0.5-1.5%.

[0033] Preferably, the initiator is any one of dibenzoyl peroxide, tert-butyl perbenzoate, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.

[0034] As a preferred embodiment of the PP composite material of the present invention, the PP composite material further comprises 0-1 part of an antioxidant.

[0035] As a preferred embodiment of the PP composite material of the present invention, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168.

[0036] Preferably, the mass ratio of the antioxidant 1010 to the antioxidant 168 is (1-2):1.

[0037] In the second aspect of the present invention, the present invention also provides a method for preparing the PP composite material, which comprises the following steps: weighing the raw materials, mixing them and sending them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain the PP composite material.

[0038] As a preferred embodiment of the preparation method of the present invention, the parameters of the twin-screw extruder are: feeding speed is 5-200 kg / h; extrusion temperature is 170-210° C.; screw speed is 300-500 rpm.

[0039] In the third aspect of the present invention, the present invention also provides the use of the PP composite material in preparing an adhesive.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] A PP composite material provided by the present invention uses a PP resin within a specific intrinsic viscosity range as a matrix, and is compounded with a PP graft, a PE resin and a tackifying resin, so that the PP composite material can achieve excellent bonding performance and formability, and the obtained product has high peel strength and good formability; specifically, the obtained product has a peel strength of more than 135N / m and a melt strength of more than 20NM; and the preparation method of the composite material provided by the present invention is simple, which is conducive to actual production. DETAILED DESCRIPTION

[0042] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0043] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0044] PP-1: SP179, melt flow rate 9g / 10min, Qilu Petrochemical;

[0045] PP-2: K6606 melt flow rate is 6g / 10min, Sinopec;

[0046] PP-3: B8101, melt flow rate 0.4g / 10min, Sinopec;

[0047] PP-4: K1008, melt flow rate 10g / 10min, Maoming Petrochemical;

[0048] PP-5: RP346R, melt flow rate 25g / 10min, Basel;

[0049] PP graft-1: melt flow rate is 40g / 10min, the mass percentage of ethylene in the PP matrix resin is 10%, homemade;

[0050] PP graft-2: melt flow rate is 60g / 10min, the mass percentage of ethylene in the PP matrix resin is 15%, homemade;

[0051] PP graft-3: melt flow rate is 90g / 10min, the mass percentage of ethylene in the PP matrix resin is 20%, homemade;

[0052] PP graft-4: melt flow rate is 20g / 10min, the mass percentage of ethylene in the PP matrix resin is 5%, homemade;

[0053] PP graft-5: melt flow rate is 40g / 10min, the mass percentage of ethylene in the PP matrix resin is 0%, homemade;

[0054] PP graft-6: melt flow rate is 150g / 10min, the mass percentage of ethylene in the PP matrix resin is 10%, homemade;

[0055] PE-1: LLDPE 3518PA, melt flow rate 3.5g / 10min, melt strength 45NM, Exxon;

[0056] PE-2: LLDPE 7042, melt flow rate 2g / 10min, melt strength 35NM, Sinopec;

[0057] PE-3: HDPE P4406C, melt flow rate 0.11g / 10min, melt strength 40NM, Maoming Petrochemical;

[0058] PE-4: LLDPE DMDA8007, melt flow rate 8g / 10min, melt strength 32NM, Guangzhou Petrochemical;

[0059] PE-5: LLDPE 7042, melt flow rate 2g / 10min, melt strength 28NM, Sinopec;

[0060] PE-6: LLDPE 0015XC, melt flow rate 15g / 10min, melt strength 35NM, Exxon;

[0061] Tackifying resin-1: petroleum resin, ESCOREZ 1000, Shanghai Jinsen;

[0062] Tackifying resin-2: EVA V 6110M, Yangzi Petrochemical;

[0063] Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, commercially available.

[0064] Examples 1-17 and Comparative Examples 1-8

[0065] The component contents (parts by weight) of Examples 1-17 and Comparative Examples 1-8 of the present invention are shown in Table 1-2;

[0066] Table 1

[0067]

[0068]

[0069] Table 2

[0070]

[0071] The preparation of PP grafted material is as follows:

[0072] Preparation of PP graft-1: PP base resin (ethylene mass percentage is 10%, manufacturer is Sinopec, model is PP M180R), initiator and maleic anhydride are mixed in a mass ratio of 100:0.1:1.5, melt-extruded at a temperature of 190°C, and then drawn into strips and pelletized to obtain PP graft-1;

[0073] Preparation of PP graft-2: PP matrix resin (ethylene mass percentage of 15%, manufacturer: Ningmei Shenhua, model PP 2500H), initiator and maleic anhydride were mixed in a mass ratio of 100:0.1:1.5, melt-extruded at a temperature of 190°C, and then stretched and pelletized to obtain PP graft-2;

[0074] Preparation of PP graft-3: PP matrix resin (ethylene mass percentage is 20%, manufacturer is Sinopec, model is PP 8101), initiator and maleic anhydride are mixed in a mass ratio of 100:0.1:1.5, melt-extruded at a temperature of 190°C, and then drawn into strips and pelletized to obtain PP graft-3;

[0075] Preparation of PP graft-4: PP base resin (ethylene mass percentage is 5%, the manufacturer is Sinopec, model is PP M500), initiator and maleic anhydride are mixed in a mass ratio of 100:0.1:1.5, and then melt-extruded at a temperature of 190°C, followed by drawing and pelletizing to obtain PP graft-4;

[0076] Preparation of PP graft-5: PP base resin (ethylene mass percentage is 0%, manufacturer is Sinopec, model is PP L5E89), initiator and maleic anhydride are mixed in a mass ratio of 100:0.1:1.5, melt-extruded at a temperature of 190°C, and then drawn into strips and pelletized to obtain PP graft-5;

[0077] Preparation of PP graft-6: PP base resin (ethylene mass percentage is 10%, manufacturer is Sinopec, model is PP M180R), initiator and maleic anhydride are mixed in a mass ratio of 100:0.15:0.5, melt-extruded at a temperature of 190°C, and then drawn into strips and pelletized to obtain PP graft-6;

[0078] The preparation methods of the composite materials provided in Examples 1-17 and Comparative Examples 1-8 are as follows:

[0079] After weighing each raw material, add it into a mixer and mix it evenly, then send it into a twin-screw extruder, adjust the feeding rate of the twin-screw extruder to 300kg / hour, and obtain a PP composite material through extrusion, drawing, cooling, pelletizing and drying. The parameters of the twin-screw extruder are as follows: extrusion temperature is 190°C; screw speed is 350rpm.

[0080] Effect example

[0081] The effect examples of the present invention verify the performance of the products prepared in the embodiments and comparative examples; the test items include the following aspects:

[0082] 1. Peel strength: tested according to standard GB / T 2792-2014;

[0083] 2. Good or bad forming: Adding the composite material into the film blowing machine, if the film can be stably blown and the film bubble is not broken, it means good forming. If the film is unstable, has holes, and is difficult to form, it means poor forming.

[0084] 3. Melt strength: measured by melt strength tester, at 190℃, record the force when the melt bundle is pulled apart. The force when the melt bundle breaks is defined as "melt strength";

[0085] The test results are shown in Table 3;

[0086] Table 3

[0087]

[0088]

[0089] It can be seen from Table 3 that when the technical solution of the present invention is adopted, the obtained product has excellent comprehensive effects, not only can it meet the high peel strength, but also the product has excellent formability. The peel strength of the obtained product is above 135N / m, and the melt strength is above 20NM;

[0090] It can be seen from Examples 1-5 and Comparative Examples 1-4 that the mass parts of the components have a significant effect on the molding and bonding strength of the product. When the mass parts of the components are further preferably 45-60 parts of PP resin, 25-35 parts of PP grafts, 10-15 parts of tackifying resin, and 8-12 parts of PE resin, the comprehensive effect of the obtained product is more excellent, the peel strength is above 152N / m, and the melt strength is above 22NM; when the amount of PP grafts added in Comparative Example 1 is too little, the peel strength is poor, only 98N / m, which is 36.77% lower than that in Example 1, indicating that the material has poor bonding performance. When the amount of PP grafts added in Comparative Example 2 is too much, the bonding strength is also low, and the molding is also poor, and the melt strength is also low; when the amount of PE resin added in Comparative Example 3 is too little, the melt strength is low and the molding performance is poor. When the amount of PE resin added in Comparative Example 4 is too much, although it is good for molding, the peel strength decreases, which is 17.42% lower than that in Example 1.

[0091] It can be seen from Example 1, Examples 7-9 and Comparative Example 5 that the melt flow rate of the PP resin will also affect the performance of the product. When the melt flow rate of the PP resin is further preferably 6-9 g / 10 min, the comprehensive performance of the obtained product is better, and the peel strength of the obtained product is above 155 N / m; when the melt flow rate of the PP resin is not within the range given in the present invention, compared with Example 1, the product prepared in Comparative Example 5 has poor molding;

[0092] It can be seen from Example 1, Examples 10-13 and Comparative Example 6 that in the PP graft, not only the melt flow rate of the PP graft but also the mass percentage of ethylene in the PP matrix resin will affect the performance of the product. When the melt flow rate of the PP graft is further preferably 40-60 g / 10 min and the mass percentage of ethylene in the PP matrix resin is 10-15%, the comprehensive performance of the obtained product is better and the peel strength of the obtained product is above 155 N / m; when the melt flow rate of the PP graft or the mass percentage of ethylene in the PP matrix resin is not within the range given in the present invention, compared with Example 1, the peel strength of the products prepared in Comparative Examples 6-7 decreases by 11.61-31.61%;

[0093] It can be seen from Example 1, Examples 15-17 and Comparative Examples 7-8 that the melt flow rate and melt strength of the PE resin will also affect the performance of the product. When the melt flow rate of the PE resin is further preferably 2-3.5 g / 10 min, the comprehensive performance of the obtained product is better, and the peel strength of the obtained product is above 154 N / m; when the melt flow rate or melt strength of the PE resin is not within the range given in the present invention, the obtained product has poor molding.

[0094] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PP composite material, characterized in that: The PP composite material comprises the following components in parts by weight: PP resin 40-70 parts, PP grafted material 20-40 parts, tackifying resin 8-20 parts, PE resin 5-15 parts; The melt flow rate of the PP resin tested at 230°C / 2.16kg according to ISO 1133-1-2011 is ≤15g / 10min; The PP graft is a maleic anhydride grafted PP matrix resin, and the melt flow rate of the PP graft is less than 100 g / 10 min when tested under the conditions of 230° C. / 0.325 kg according to ISO 1133-1-2011; The PE resin is tested according to ISO 1133-1-2011 under the conditions of 190° C. / 2.16 kg, and the melt flow rate is 0.1-10 g / 10 min, and the melt strength is greater than 30 NM.

2. The PP composite material according to claim 1, characterized in that: The PP composite material comprises the following components in parts by weight: 45-65 parts of PP resin, 25-35 parts of PP grafts, 10-15 parts of tackifying resin, and 8-12 parts of PE resin.

3. The PP composite material according to claim 1, characterized in that: At least one of the following (a)-(c): (a) the melt flow rate of the PP resin is 0.3-12 g / 10 min; (b) the melt flow rate of the PP graft is 15-95 g / 10 min, the PP matrix resin is a copolymer of propylene and ethylene, and the mass percentage of ethylene is 3-25%; (c) The melt flow rate of the PE resin is 0.10-8.5 g / 10 min.

4. The PP composite material according to claim 1, characterized in that: The tackifying resin is at least one of rosin resin, petroleum resin, EVA, EMA, and EEA.

5. The PP composite material according to claim 1, characterized in that: The preparation method of the PP grafted product comprises the following steps: mixing a PP matrix resin, an initiator and maleic anhydride, and then performing melt extrusion, strip drawing and pelletizing to obtain the PP grafted product.

6. The PP composite material according to claim 1, characterized in that: The PP composite material also includes 0-1 parts of antioxidant.

7. The PP composite material according to claim 6, characterized in that: The antioxidant is a mixture of antioxidant 1010 and antioxidant 168.

8. The method for preparing the PP composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: weighing the raw materials, mixing them and sending them into a twin-screw extruder, and performing extrusion, strip drawing, cooling, pelletizing and drying to obtain a PP composite material.

9. The preparation method according to claim 8, characterized in that: The parameters of the twin-screw extruder are: feeding speed is 5-200kg / h; extrusion temperature is 170-210°C; screw speed is 300-500rpm.

10. Use of the PP composite material according to any one of claims 1 to 7 in the preparation of an adhesive.

Citation Information

Patent Citations

  • Method for preparing polypropylene / maleic anhydride melt grafting high condensing pre-mixed master batch

    CN101423590A

  • Preparation method of maleic anhydride drafted polypropylene resin graft polymer

    CN101724128A